Restaurants' disclosure of nutritional information as a corporate social responsibility initiative: Customers' attitudinal and behavioral responses. (May 2016) - Kim, Eojina; Ham, Sunny
Highlights: Investigates disclosure of nutritional information, as a CSR of restaurants, and customers' responses toward the restaurants. An empirical evidence was obtained from 636 casual dining restaurant customers. Demonstrates that customers perceive disclosure of NI as a CSR by restaurants. BI and BT mediate between customer CSR perception toward disclosure of NI of restaurants and CL. Abstract: This study aims to understand the relationship between menu labeling as a corporate social responsibility initiative of restaurants and customers' attitudinal and behavioral responses toward restaurants. A conceptual model was developed, including five hypotheses that relate the perception of the disclosure of nutritional information as corporate social responsibility (CSR) to brand trust, brand image, and loyalty toward the restaurant. Data were collected from 636 customers of casual dining restaurants in Korea. Confirmatory factor analysis and structural equation modeling were used to test the proposed theoretical relationships. Customers' perceptions of restaurants' CSR initiatives in the form of the disclosure of nutritional information affect their loyalty, while brand image and brand trust are affected by such CSR disclosure by restaurants. This study is one of the few to empirically research the concept of menu labeling from a CSR perspective as a basis for providing a healthy eating environment in restaurants. Specifically, from a social responsibility perspective, this study contributes to the existing knowledge by examining the impact of restaurants' labeling of menus on customers' cognitive and behavioral responses. The results provide practitioners with effective strategies to eventually enhance customer loyalty to restaurants through enhanced brand images and brand trust, and to sustain CSR initiatives as effective marketing strategies.